2005
DOI: 10.1063/1.1896405
|View full text |Cite
|
Sign up to set email alerts
|

Effective slip on textured superhydrophobic surfaces

Abstract: We study fluid flow in the vicinity of textured and superhydrophobically coated surfaces with characteristic texture sizes on the order of 10μm. Both for droplets moving down an inclined surface and for an external flow near the surface (hydrofoil), there is evidence of appreciable drag reduction in the presence of surface texture combined with superhydrophobic coating. On textured inclined surfaces, the drops roll faster than on a coated untextured surface at the same angle. The highest drop velocities are ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
135
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 232 publications
(147 citation statements)
references
References 8 publications
8
135
0
1
Order By: Relevance
“…However, the numerous experimental studies in the literature have reported (many erroneously, as discussed in Sects. 3.2.5 and 3.3.5) a wide range of slip lengths spanning from tens of nanometers to even millimeters on SHPo surfaces consisting of regular (periodic) structures (Ou et al 2004;Ou and Rothstein 2005;Choi et al 2006;Davies et al 2006;Truesdell et al 2006;Maynes et al 2007;Steinberger et al 2007;Byun et al 2008;Lee et al 2008;Tsai et al 2009;Jung and Bhushan 2010;Lee and Kim 2011a;Kashaninejad et al 2012;Kim and Hidrovo 2012;Maali et al 2012;Karatay et al 2013;Bolognesi et al 2014;Lee and Kim 2014) or random structures (Watanabe et al 1999(Watanabe et al , 2003Gogte et al 2005;Choi and Kim 2006a;Joseph et al 2006;Bhushan et al 2009;Govardhan et al 2009;Shirtcliffe et al 2009;Wang et al 2009;Kim and Hwang 2010;Li et al 2010;Wang and Bhushan 2010;Ming et al 2011;Srinivasan et al 2013). Sometimes orders-of-magnitude differences in the measured slip lengths were reported even on structurally similar SHPo surfaces (e.g., Lee et al 2008vs.…”
Section: The Motivation Of the Critical Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the numerous experimental studies in the literature have reported (many erroneously, as discussed in Sects. 3.2.5 and 3.3.5) a wide range of slip lengths spanning from tens of nanometers to even millimeters on SHPo surfaces consisting of regular (periodic) structures (Ou et al 2004;Ou and Rothstein 2005;Choi et al 2006;Davies et al 2006;Truesdell et al 2006;Maynes et al 2007;Steinberger et al 2007;Byun et al 2008;Lee et al 2008;Tsai et al 2009;Jung and Bhushan 2010;Lee and Kim 2011a;Kashaninejad et al 2012;Kim and Hidrovo 2012;Maali et al 2012;Karatay et al 2013;Bolognesi et al 2014;Lee and Kim 2014) or random structures (Watanabe et al 1999(Watanabe et al , 2003Gogte et al 2005;Choi and Kim 2006a;Joseph et al 2006;Bhushan et al 2009;Govardhan et al 2009;Shirtcliffe et al 2009;Wang et al 2009;Kim and Hwang 2010;Li et al 2010;Wang and Bhushan 2010;Ming et al 2011;Srinivasan et al 2013). Sometimes orders-of-magnitude differences in the measured slip lengths were reported even on structurally similar SHPo surfaces (e.g., Lee et al 2008vs.…”
Section: The Motivation Of the Critical Reviewmentioning
confidence: 99%
“…4b, micro-particle image velocimetry (micro-PIV) has been widely used as a direct way to measure a velocity profile close to the wall and extract a slip length from the measured velocity profile (Gogte et al 2005;Ou and Rothstein 2005;Joseph et al 2006;Byun et al 2008;Tsai et al 2009;Karatay et al 2013;Bolognesi et al 2014). In this method, fluorescent particles dispersed in water are used as a tracer for the liquid velocity.…”
Section: Measurement Techniques Of Slip Lengthmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the lower dynamic viscosity of air compared to water the trapped air layer on a superhydrophobic surface has a lubricating effect on the flow over it. Drag reducing properties of superhydrophobic surfaces have been observed experimentally in microfluidic devices (Choi, Westin & Breuer 2003;Ou, Perot & Rothstein 2004;Ou & Rothstein 2005;Joseph et al 2006;Daniello, Waterhouse & Rothstein 2009;Govardhan et al 2009;Tsai et al 2009;Rothstein 2010) and for coated objects, such as hydrofoils (Gotge et al 2005), settling spheres (McHale et al 2009) and cylinders (Muralidhar et al 2011), covering flow regimes from laminar to turbulent. In a stable configuration, i.e.…”
Section: Introductionmentioning
confidence: 99%